Normalization of Peri-Arteriovenous Malformation Hemodynamics Prior to Direct Microsurgery: 2-Dimensional Operative Video. Issue 6 (24th September 2021) - Rahme, Rudy J; Turcotte, Evelyn L; Patra, Devi P; Welz, Matthew E; Batjer, H Hunt; Bendok, Bernard R
Abstract: Arteriovenous malformations (AVMs) are highly complex vascular lesions characterized by abnormal connections between arteries and an intervening nidus. Definitive and safe treatment of AVMs may require the combination of multiple treatment modalities to address the various complex features of the AVM. 1 Endovascular embolization can be used as an adjuvant to surgery in order to control deep feeders, reduce flow, and address high-risk features such as aneurysms. In addition, by progressively reducing the AVM flow, staged embolization can lead to normalization of peri-AVM hemodynamics and therefore may decrease the risk of postresection hemorrhage. 2, 3 In this operative video, we present a case of a 41-yr-old female who presented with progressively worsening left-sided hemiparesis. Magnetic resonance imaging (MRI) and angiography revealed a complex right fronto-parietal AVM with significant associated edema, likely due to the vascular steal phenomenon. The area of edema, which included the motor cortex, was thought to be at high risk for postoperative hemorrhage from normal perfusion pressure breakthrough. We therefore decided to proceed with staged presurgical embolization to gradually normalize the perilesional hemodynamics, and therefore possibly reduce the risk of postoperative morbidity. The patient underwent 3 embolization sessions at 6-wk intervals. An MRI after the last embolization showed near-complete resolution of the fluid-attenuated inversion-recovery (FLAIR) signal around the AVM. Microsurgical resection was performed on the day after the last embolization. The patient tolerated the procedure well and was discharged at her neurological baseline with mild contralateral hemiparesis, which has continued to improve at follow-up. Postoperative angiography showed complete resection of the AVM. The patient consented to the procedure as shown in this operative video and gave informed written consent for use of her images in publication.